Enabling Sustainable Chemistry with Ionic Liquids and Deep Eutectic Solvents: A Fad or the Future? - Quintana, Aline Andrea; Sztapka, Alaina Maria; Ebinuma, Valéria de Carvalho Santos [UNESP]; Agatemor, Christian (Wiley, 2022)
Ionic liquids (ILs) and deep eutectic solvents (DESs) debuted with a promise of a superior sustainability footprint due to their low vapor pressure. However, their toxicity and high cost compromise this footprint, impeding their real-world applications. Fortunately, their property tunability through a rational selection of precursors, including bioderived ones, provides a strategy to ameliorate toxicity, lower cost, and endow new functions. This Review discusses whether ILs and DESs are sustainable solvents and how they contribute to sustainable chemical processes.
Keywords: Deep Eutectic Solvents; Green Chemistry; Ionic Liquids; Neoteric Solvents; Sustainable Chemistry